Projectile interaction effects in out-of-plane excitation-ionization of helium. (23rd September 2015) - Harris, A L; Esposito, T P
Abstract: We present theoretical three-dimensional fully differential cross sections for electron-impact excitation-ionization of helium when the ionized electron is found outside of the scattering plane. Using our first born approximation and 4-body distorted wave models, we examine the effect of the projectile in the initial and final states. Our calculations show that the inclusion of projectile interactions results in an increase in the magnitude of the recoil lobe.